의료시장 개방에 따른 국내병원 대응에 대한 치위생과 학생들의 견해에 관한 연구 - 윤현서; Hyun Seo Yoon; 김동열; Dong Yeol Kim (Chiwisaeng gwahakoeji, 2009)
The purpose of this study was to examine the views of dental hygiene students about the possible countermeasure of domestic hospitals for the opening of the medical market. The subjects in this study were 269 dental hygiene sophomores, juniors and seniors at two different colleges in the region of Busan. The findings of the study were as follows: The opening of the medical market and views of possible countermove, whether they agreed to that or not made a statistically significant difference to their opinions on the necessity of customer-oriented marketing strategy(p=0.023), analysis of foreign medical markets/attempt to make inroads into the markets(p<0.000) and the improvement of the quality of medical services/the diversification of the services(p=0.025). As to an intention of going to a foreign hospital, they had a statistically significantly different intention about whether to go to a foreign hospital regardless of medical bills(p<0.000), whether to consult a doctor in a foreign hospital after going to a domestic hospital first (p<0.000), whether to consider the distance between their houses and a foreign hospital(p=0.05) and whether to take considerations on the assistance of an interpreter(p=0.023). In regard to preference for foreign hospitals, American hospitals ranked first(41.9), followed by Australian hospitals(19.9) and Canadian ones(14.2). 부산지역에 소재한 2개 대학 치위생과 1, 2, 3학년에 재학 중인 학생 269명을 대상으로 의료시장 개방에 따른 국내 병원의 대응 방안에 대한 조사 분석의 결과는 다음과 같다. 1. 찬반의견과 대응방안에서 고객만족 병원마케팅의 수립(p=0.023), 해외의료시장 분석 및 진출 모색(p<0.000), 의료서비스의 질 개선 및 다양화(p=0.025)에서 통계적으로 유의한 차이를 보였다. 2. 치과 병 의원 실습 및 아르바이트 경험 유무와 대응 방안은 경험이 있는 경우 병원이미지 차별화(p=0.01), 국민건강보험 수가 현실화(p=0.004), 보험 급여대상 확대(p=0.012)평점이 높고 통계적으로 유의하였다. 3. 학년과 대응방안은 학년이 높을수록 병원이미지 차별화(p=0.009), 국민건강보험 수가 현 실화(p=0.004), 보험 급여대상 확대(p=0.045) 평점이 높고, 통계적의로 유의한 차이를 보 였다. 4. 보건/의료관련 기사에 대한 관심 유무와 대응방안은 관심이 있는 경우 경영의 합리화 (p<0.000), 중소병원과 대형 병원간 협력관계 구축(p=0.027), 고객만족 병원마케팅의 수립 (p<0.000), 의료시장 변천에 따른 정책 개발(p=0.001), 해외의료시장 분석 및 진출모색(p=0.001), 의료서비스의 질 개선 및 다양화 (p<0.01), 직원 친절서비스교육 및 훈련 (p=0.01), 병원의 이미지 차별화(p=0.012), 진료예약제의 개선(p=0.025), 병원 부대시설 의 개선(p=0.029), 의사들의 의식 개혁(p=0.007)에서 평점이 높았으며 통계적으로 유의한 차이를 보였다. 5. 외국 병원 이용의사에서는 진료비와 상관없이 이용 (p<0.000), 국내병원 진단 후 외국병 원에서 재 진단 유무(p<0.000), 거주지와 거리부분(p=0.05), 의료서비스가 진료비와 진료 비(p=0.005), 통역사의 도움부분(p=0.023)에서 통계적으로 유의하였다. 외국 병원 선호 국 가에서 1위 미국(41.9), 2위 호주(19.9), 3위 캐나다(14.2)순으로 나타났다.